Electrochemical Analysis for Enhancing Interface Layer of Spinel LiNi0.5Mn1.5O4 Using p-Toluenesulfonyl Isocyanate as Electrolyte Additive - Xiao, Zhe; Wang, Renheng; Li, Yan; Sun, Yiling; Fan, Shuting; Xiong, Keyu; Zhang, Han; Qian, Zhengfang (Frontiers in Chemistry, 2019)
LiNi0.5Mn1.5O4 (LNMO) is a potential cathode material for lithium-ion batteries with outstanding energy density and high voltage plateau (˃4.7 V). However, the interfacial side reaction between LNMO and the liquid electrolyte seriously causes capacity fading during cycling at the high voltage. Here, p-toluenesulfonyl isocyanate (PTSI) is used as the electrolyte additive to overcome the above problem of LNMO. The results show that the specific capacity of LNMO/Li cell with 0.5 wt.% PTSI at the first cycle is effectively enhanced 36.0 mAh/g and has better cycling performance than that without PTSI at 4.98 V. Also, a stable solid electrolyte interface (SEI) film derived from PTSI is generated on the electrode surface, which could alleviate the strike of hydrofluoric acid (HF) caused by electrolyte decomposition. These results are explained by the molecular structure of PTSI, which contains SO3. The S=O groups can delocalize the nitrogen nucleus to block the reactivity of PF5.